Preparation method of polyvinyl pyrrolidone-high dielectric constant composite film and high dielectric constant photovoltaic encapsulation film
By introducing polyvinylpyrrolidone on the surface of high dielectric constant substances and preparing composite films by electrospinning process, the problem of insufficient improvement of PID of photovoltaic modules in the prior art is solved, and efficient charge storage and anti-PID performance are achieved.
Patent Information
- Application Number
- CN202411456950.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The prior art has shortcomings in improving potential induced attenuation (PID). Adding SiO2 films with high refractive SiNx layer will reduce the cell conversion efficiency. Too little or too much metal ion trapping agent will affect the light transmittance and crosslinking density of the adhesive film, and the various crosslinking accelerators have limited effect on improving the charge migration problem of PID-p.
The polyvinylpyrrolidone-high dielectric constant composite film was adopted to enhance its compatibility and polarization effect with the EVA film by introducing polyvinylpyrrolidone on the surface of the high dielectric constant substance, and then directly hot-pressed bonded with EVA after preparing the composite film through electrospinning process, solving the agglomeration and dispersion of high dielectric constant substances in EVA.
The volume resistivity and PID resistance of the packaging film are significantly improved, the anti-PID effect of the components is enhanced, making it close to POE, and the dispersion and compatibility problems of high dielectric constant materials in the film are solved.
Smart Images

Figure CN119162739B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high dielectric constant composite film, which can be used for preparing a high dielectric constant photovoltaic encapsulation adhesive film. Background Art
[0002] Potential Induced Degradation (PID) is a common failure phenomenon in photovoltaic modules. It mainly occurs when there is a high potential difference between the internal battery and the external metal frame of the module. In a high temperature and high humidity environment, this electric field will accelerate the movement and diffusion of positively charged ions, resulting in module power attenuation. There are generally three mechanisms of PID mode: 1. Polarization-type (PID-p), mainly because the active area of the semiconductor (solar cell) is affected, the passivation effect deteriorates, and it will recover under light; 2. PID-shunt (PID-s), Na+ and other metal ions migrate to form a PN junction leakage current channel of the solar cell, resulting in attenuation; 3. Ionization corrosion, mainly because water vapor corrodes the cell or metal ions are deposited on the surface of the cell or on the passivation layer under high temperature and high humidity conditions, resulting in the electrical performance of the cell attenuation.
[0003] For the improvement of potential induced degradation (PID), photovoltaic cells can use a high-refractive SiNx layer with a sufficiently thin SiO2 film to improve it. The principle is to dissipate the accumulated charge through the tunnel effect. In terms of component materials: the impact of PID is generally delayed by improving the encapsulation film. The volume resistivity or water permeability of the film can be increased to improve the film performance. For the improvement of the encapsulation film, a variety of cross-linking promoters can also be used to further increase the cross-linking density of the encapsulation film, thereby enhancing the barrier capacity of the encapsulation film and inhibiting the migration of ions in the film, thereby reducing the occurrence of system PID problems. For example, the cross-linking density of the EVA cross-linking system can be increased by adding auxiliary cross-linking agents such as acrylates. In addition, some acrylates have a structure similar to crown ethers that can accommodate Na+ ions and have an inhibitory effect on migration; for the improvement of the encapsulation film, metal ion scavengers can also be added by physical methods. Metal ion scavengers, including aluminosilicates, hydrated oxides, and polyvalent metal acid salts, are added to the photovoltaic encapsulation film to capture mobile metal cations such as Na+, K+, and Ca2+, so that they do not migrate to the surface of the cell to cause passivation failure, thereby inhibiting PID problems. For example, zirconium phosphate has a large surface area and rich surface charge, which can adsorb or attract Na+ ions, reduce the damage of Na+ ions to the anti-reflection layer and passivation layer when reaching the surface of the battery cell, and delay PID.
[0004] The above existing technologies for improving potential induced decay have the following shortcomings: using a high-refractive SiNx layer with a sufficiently thin SiO2 film to improve the battery end will reduce the conversion efficiency of the battery cell; if the amount of metal ion scavenger added in the component packaging material is too small, the anti-PID effect is not obvious; if the amount added is too much, it will have a greater negative effect on the light transmittance of the film because they are all inorganic particles. Moreover, adding multiple cross-linking promoters to the component packaging material has limited effect on suppressing the PID phenomenon, especially the improvement effect on the charge migration problem of PID-p is poor.
[0005] The invention patent application with application number 202310677054.0 provides a photovoltaic module encapsulation film. The encapsulation film composition includes a matrix resin and a high dielectric material, wherein the dielectric constant of the high dielectric material is ≥10; the high dielectric material includes any one or more of organic polymer materials, carbon inorganic materials and metal inorganic materials. Since the high dielectric material is added to the encapsulation film composition and distributed in the matrix resin, the capacitance effect of the encapsulation film can be greatly enhanced. In the presence of a potential difference, a certain amount of charge can be stored, thereby reducing the charge migration to the surface of the battery cell, and effectively suppressing the PID problem of the photovoltaic module.
[0006] However, when high dielectric constant materials such as barium titanate, barium strontium titanate, and silicon carbide are added to the encapsulation film, there are dispersion and compatibility problems. The main manifestation is that the compatibility of inorganic high dielectric constants with EVA films is poor, and the polarization effect of high dielectric constants is not obvious; on the other hand, inorganic high dielectric constant powders agglomerate, causing the transmittance to be affected, the body resistance values in different regions vary greatly, and the polarization regions are unevenly distributed, resulting in unstable anti-PID performance of the components. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a method for preparing a polyvinyl pyrrolidone-high dielectric constant composite film. Polyvinyl pyrrolidone is introduced onto the surface of a high dielectric constant material, so as to increase the compatibility of the high dielectric constant material with EVA, and polyvinyl pyrrolidone can activate the polarization effect of the high dielectric constant. Meanwhile, compared with directly adding or granulating with EVA, the electrostatic spinning process is adopted to prepare the film, and then the film is directly hot-pressed and laminated with EVA, thereby solving the problem of agglomeration of the high dielectric constant material in EVA, improving the dispersion performance of the high dielectric constant inorganic material in EVA, and improving the volume resistivity and anti-PID performance of the film.
[0008] The present invention also proposes a high dielectric photovoltaic encapsulation film, which uses a polyvinyl pyrrolidone-high dielectric constant composite film and EVA for direct hot pressing. Since a high dielectric constant substance is added to the polyvinyl pyrrolidone-high dielectric constant composite film material, the capacitance effect of the encapsulation film is enhanced. In the presence of a potential difference, a certain amount of charge can be stored, thereby reducing the charge migration to the surface of the battery cell, and effectively suppressing the PID problem of the photovoltaic module.
[0009] The present invention also provides a photovoltaic module using the high dielectric photovoltaic encapsulation film.
[0010] The technical solution adopted by the present invention is:
[0011] A method for preparing a polyvinyl pyrrolidone-high dielectric constant composite film, wherein a high dielectric constant substance is added to a photovoltaic encapsulation polymer material to prepare a polyvinyl pyrrolidone-high dielectric constant composite film, the process comprising:
[0012] Step S1, hydroxylating the surface of a high dielectric constant material raw material to obtain a high dielectric constant material a with a hydroxyl group coated on the surface; the high dielectric constant material is any one of barium titanate, barium strontium titanate, silicon carbide, lead zirconate titanate, titanium dioxide, zirconium dioxide and silicon dioxide, or a mixture of two or more thereof;
[0013] Step S2, performing surface modification treatment on the high dielectric constant material a obtained in step S1: adding a vinyl silane coupling agent to introduce double bonds on the surface of the high dielectric constant material, adding a vinyl pyrrolidone monomer to polymerize the surface of the high dielectric constant material, and coating the surface with a polyvinyl pyrrolidone polymer to obtain an active high dielectric constant material b;
[0014] Step S3, mixing the high dielectric constant material b obtained in step S2 with EVA and dissolving them in DMF / dichloromethane solvent, stirring them magnetically at 35-45° C. to obtain a uniform solution, and then obtaining a polyvinyl pyrrolidone-high dielectric constant composite film through an electrospinning process.
[0015] In the polyvinyl pyrrolidone-high dielectric constant composite film preparation method, in step S1, the surface hydroxylation treatment process of the high dielectric constant material is as follows: the high dielectric constant material raw material and the H2O2 solution are first ultrasonically dispersed, and then stirred at 90-100°C for 3-4 hours with a magnetic stirrer. After the reaction system is cooled to room temperature, the product is filtered and centrifugally washed with ethanol and deionized water for multiple times, and then the washed product is placed in a drying oven at 80°C to obtain a high dielectric constant material a with surface hydroxylation.
[0016] The method for preparing the polyvinyl pyrrolidone-high dielectric constant composite film, in step S2, the high dielectric constant substance a is subjected to wet surface modification treatment, and the process is as follows: vinyl silane and ethanol are mixed in a certain proportion to obtain a coupling agent concentration of 0.5-5% solution, and then an acid catalyst and the high dielectric constant substance a are added and stirred evenly, and the silane coupling agent is hydrolyzed to react with the surface of the high dielectric constant substance to introduce double bonds; then vinyl pyrrolidone and a free radical initiator are added, and the reaction is carried out in an ethanol solution at 60-120°C for 1-3h to obtain the high dielectric constant substance b.
[0017] The vinyl silane coupling agent is one of 171 vinyl trimethoxy silane and 151 vinyl triethoxy silane or a mixture of the two.
[0018] The polyvinyl pyrrolidone-high dielectric constant composite film preparation method comprises the following conditions: pH is 3-5, the coupling agent dosage is 1-10% of the mass dosage of the high dielectric constant material, and the treatment is carried out at 80°C for 2h; the vinyl pyrrolidone coating rate of the high dielectric constant material a is controlled at 1-10%.
[0019] The polyvinyl pyrrolidone-high dielectric constant composite film preparation method, in step S2, the spinning voltage of the high dielectric constant material b is 10-30 kV, the spinning solution flow rate is 1-5 mL / h, and a polypyrrolidone / high dielectric constant material composite film is obtained, which stays on the release paper and has a film thickness of 0.05-0.3 mm.
[0020] In the polyvinyl pyrrolidone-high dielectric constant composite film preparation method, the dielectric constant range of the added high dielectric constant material is: 3-3700; the added amount is 0.001%-0.5% of the mass of the matrix resin; and the particle size is 30-500nm.
[0021] A high dielectric constant photovoltaic encapsulation adhesive film is prepared by laminating the polyvinyl pyrrolidone-high dielectric constant composite film prepared above between two layers of EVA adhesive films by hot pressing to obtain a high dielectric constant EVA adhesive film with a three-layer structure.
[0022] A method for preparing a high dielectric photovoltaic encapsulation film, comprising:
[0023] EVA resin: 98 parts; the EVA resin has a melt index of 25 and a VA content of 28;
[0024] Cross-linking agent: one or a mixture of tert-butyl peroxycarbonate-2-ethylhexanoate TAEC and tert-butyl peroxycarbonate-2-ethylhexyl carbonate TBEC, added in an amount of 0.4-0.8 parts;
[0025] Auxiliary cross-linking agent: triallyl isocyanurate TAIC, added amount 0.3-0.8 parts;
[0026] Crosslinking promoter: one or more of tripropylene glycol diacrylate, propoxylated glycerol triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate, etc., added in an amount of 0.4-1.2 parts;
[0027] Coupling agent: one or more of 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, added in an amount of 0.2-0.5 parts;
[0028] Light stabilizer: one or two of 292 and 770, added in an amount of 0.05-0.2 parts;
[0029] Antacid: 0.05-0.4 parts of magnesium hydroxide; the surface of magnesium hydroxide is treated with silane (3-methacryloxypropyltriethoxysilane), and the coating rate is 5%;
[0030] The EVA resin is added to the mixing tank, the liquid additive is evenly mixed and then sprayed onto the EVA particles, a heating jacket at 45-60°C is used for heat preservation and absorption for 2 hours, and then the anti-acid masterbatch is added and mixed for 2 hours and allowed to stand, the extruder module temperature is set at 70-75°C, the film outlet temperature is set at 90-95°C for casting, and the screw extrusion speed and metering pump are used to adjust the film weight and thickness;
[0031] Then, the polyvinyl pyrrolidone-high dielectric constant composite film and two layers of 200 g (250 μm thick) EVA films were calendered and rolled.
[0032] A photovoltaic component is encapsulated by the high dielectric photovoltaic composite encapsulation film as described above.
[0033] Beneficial effects of the invention:
[0034] 1. The method for preparing a polyvinyl pyrrolidone-high dielectric constant composite film of the present invention provides a polyvinyl pyrrolidone-high dielectric constant composite film. By introducing polyvinyl pyrrolidone on the surface of a high dielectric constant material coated with hydroxyl groups, the advantage is that compared with a single high dielectric constant material, the compatibility of the high dielectric constant material with the EVA film can be enhanced, and polyvinyl pyrrolidone can activate and enhance the polarization effect of the high dielectric constant.
[0035] 2. The method for preparing polyvinyl pyrrolidone-high dielectric constant composite film of the present invention adopts electrostatic spinning process to make the film and then directly hot presses and bonds it with EVA. Compared with directly adding or granulating with EVA, it solves the agglomeration of high dielectric constant substances in EVA, improves the dispersion performance of high dielectric constant inorganic substances in EVA, and improves the volume resistivity and anti-PID performance of the film.
[0036] 3. The high dielectric photovoltaic encapsulation film of the present invention is made by electrostatic spinning and then hot-pressed with EVA film to obtain a high dielectric EVA film with better compatibility and dispersibility. The body resistance of this high dielectric constant EVA encapsulation film can be significantly increased by 1-2 orders of magnitude; the polarization effect of the high dielectric constant substance in the film can significantly improve the anti-PID effect of the component, and the anti-PID effect is close to POE. By adding a high dielectric constant substance to the film material, the capacitance effect of the encapsulation film can be enhanced. In the presence of a potential difference, a certain amount of charge can be stored, thereby reducing the charge migration to the surface of the battery cell, and effectively suppressing the PID problem of the photovoltaic module.
[0037] High dielectric constant materials such as barium titanate, barium strontium titanate, and silicon carbide are added to the packaging film, and there are dispersion and compatibility problems. Therefore, the present invention first performs a hydroxylation treatment on high dielectric constant materials such as barium titanate, barium strontium titanate, and silicon carbide, and then performs a modification treatment on them so that their surfaces are coated with polypyrrolidone, thereby enhancing the compatibility of the high dielectric constant materials with the EVA film, and finally prepares a polyvinylpyrrolidone-high dielectric constant composite film through an electrostatic spinning process, and then further prepares a high dielectric photovoltaic packaging film, thereby solving the dispersion and compatibility problems of high dielectric constant materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The figure shows a schematic diagram of the structure of the high dielectric film of the present invention;
[0039] Figure 2 Shown is a schematic diagram of the high dielectric layer composition. DETAILED DESCRIPTION
[0040] In order to make the technical concept and advantages of the invention more clearly understood, the technical solution of the invention is further described in detail below in conjunction with the accompanying drawings. It should be understood that the following embodiments are only used to explain and illustrate the preferred implementation of the invention and should not constitute a limitation on the scope of protection of the patent claim of the invention.
[0041] The film formula of the embodiment:
[0042] EVA resin: melt index 25, VA content 28. There are one or more of Hanhua 280PV, Sailbon V2825, etc.; the addition amount is 98 parts.
[0043] Cross-linking agent: one or more of tert-butyl peroxycarbonate-2-ethylhexanoate TAEC and tert-butyl peroxy-2-ethylhexyl carbonate TBEC, added in an amount of 0.4-0.8 parts;
[0044] Auxiliary cross-linking agent: triallyl isocyanurate TAIC, added in an amount of 0.3-0.8 parts;
[0045] Crosslinking promoter: one or more of tripropylene glycol diacrylate, propoxylated glycerol triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate, etc., added in an amount of 0.4-1.2 parts;
[0046] Coupling agent: one or more of 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, added in an amount of 0.2-0.5 parts;
[0047] Light stabilizer: a mixture of 292 bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and 1-methyl-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, or one or more of 770 bis-2,2,6,6-tetramethylpiperidinol sebacate, with an addition amount of 0.05-0.2 parts;
[0048] Antacid: 0.05-0.4 parts of magnesium hydroxide. The surface of magnesium hydroxide is treated with silane, and the coating rate is 5%.
[0049] Add EVA resin to the mixing tank, mix the liquid additives evenly and then spray them on the EVA particles. Heat the heating jacket at 45-60℃ for 2 hours, then add the antacid masterbatch and mix for 2 hours. Set the extruder module temperature to 70-75℃ and the film outlet to 90-95℃ for casting. The screw extrusion speed and metering pump are used to adjust the film weight and thickness. Then, the obtained polyvinyl pyrrolidone-high dielectric constant composite film is laminated between two layers of EVA film by hot pressing (the weight of the two layers of EVA film is about 200 grams and the thickness is 250 microns), calendered, and rolled. Figure 1 The figure shows a schematic diagram of the structure of the high dielectric film of the present invention; Figure 2 Shown is a schematic diagram of the high dielectric layer composition.
[0050] The preparation process of the polyvinyl pyrrolidone-high dielectric constant composite film (the high dielectric constant material in Example 1 uses barium titanate) is the process of coating the surface of the high dielectric constant material with polyvinyl pyrrolidone as follows:
[0051] The first step is to treat the surface of the high dielectric constant material (dielectric constant 3000, particle size 50nm) by hydroxylation: the raw material of the high dielectric constant material and the H2O2 solution are first dispersed by ultrasound, and then stirred at 100°C for 4 hours with a magnetic stirrer. After the reaction system is cooled to room temperature, the product is filtered and washed by centrifugation with ethanol and deionized water for several times. The washed product is then placed in a drying oven at 80°C to obtain a high dielectric constant material a with surface hydroxylation.
[0052] In the second step, the high dielectric constant material a is subjected to wet surface modification treatment: vinyl trimethoxysilane 171 and ethanol are mixed in a certain proportion to obtain a 2% coupling agent solution, barium titanate (coating rate is controlled at 5%) is added and stirred evenly, the coupling agent hydrolysis conditions are pH 4.5, hydrolysis at room temperature for 2 h; the surface modification treatment conditions are: coupling dosage is 5-10%, and treatment is carried out at 80°C for 2 h. Then it is placed in a drying oven for drying to remove residual ethanol and moisture. The high dielectric constant material is reacted with vinyl pyrrolidone and free radical initiator AIBN (0.5% of vinyl pyrrolidone) in an ethanol solution at 75°C for 2 h to obtain a high dielectric constant material b coated with polyvinyl pyrrolidone.
[0053] The vinyl silane coupling agent may also be 151 vinyl triethoxy silane, or a mixture of 171 vinyl trimethoxy silane and 151 vinyl triethoxy silane.
[0054] In the third step, the spinning voltage of the high dielectric constant material b is 25 kV and the spinning solution flow rate is 2.5 mL / h, and a polypyrrolidone / barium titanate composite film is obtained, which stays on the release paper and has a film thickness of 0.05-0.3 mm.
[0055] The implementation plan and results of adding a single barium titanate high dielectric constant material are shown in the following table:
[0056] .
[0057] Example 1 provides a high dielectric constant photovoltaic encapsulation film and a preparation method thereof, the only difference being that the high dielectric constant material is barium titanate, and the amount thereof is different. In this example, polyvinyl pyrrolidone is chemically coated on the surface of barium titanate,
[0058] Example 2 provides a high dielectric constant photovoltaic encapsulation film and a preparation method thereof, the only difference being that the high dielectric constant material is barium titanate, and the amount used is different. In this example, polyvinyl pyrrolidone is chemically coated on the surface of barium titanate,
[0059] Example 3 provides a high dielectric constant photovoltaic encapsulation film and a preparation method thereof, the only difference being that the high dielectric constant material is barium titanate, and the amount used is different. In this example, polyvinyl pyrrolidone is chemically coated on the surface of barium titanate,
[0060] Example 4 provides a high dielectric constant photovoltaic encapsulation film and a preparation method thereof, the only difference being that the high dielectric constant material is barium titanate, and the amount thereof is different. In this example, polyvinyl pyrrolidone is chemically coated on the surface of barium titanate.
[0061] Comparative Example 1: EVA film weight 400 casting, no barium titanate added. Film formula: EVA resin Hanhua 280P (melt index 25, VA content 28) added in an amount of 98 parts; crosslinking agent peroxy-2-ethylhexyl carbonate tert-butyl ester TBEC, added in an amount of 0.4-0.6 parts; auxiliary crosslinking agent TAIC, added in an amount of 0.5 parts; crosslinking promoter propoxylated glyceryl triacrylate, added in an amount of 0.6 parts; coupling agent 3-methacryloxypropyl trimethoxysilane, added in an amount of 0.3 parts; light stabilizer sebacate bis-2,2,6,6-tetramethylpiperidinol ester 770, added in an amount of 0.1 parts; antacid silane surface coated with magnesium hydroxide 0.15 parts, the coating rate is 5%. Add EVA resin to the mixing tank, mix the liquid additives evenly and spray them on the EVA particles. After absorbing the heat at 45-60℃ heating jacket for 2 hours, add the anti-acid masterbatch and mix for 2 hours, then let it stand. Set the extruder module temperature to 72℃ and the film outlet temperature to 92℃ for casting. The screw extrusion speed and metering pump are used to adjust the film weight and thickness.
[0062] Comparative Example 2 provides a high dielectric photovoltaic encapsulation adhesive film and a preparation method thereof, the only difference being that barium titanate is directly added to EVA and directly cast.
[0063] Film formula: EVA resin Hanhua 280P (melt index 25, VA content 28) added in an amount of 98 parts; cross-linking agent peroxy-2-ethylhexyl carbonate tert-butyl ester TBEC, added in an amount of 0.4-0.6 parts; auxiliary cross-linking agent TAIC, added in an amount of 0.5 parts; cross-linking promoter propoxylated glycerol triacrylate, added in an amount of 0.6 parts; coupling agent 3-methacryloxypropyl trimethoxysilane, added in an amount of 0.3 parts; light stabilizer sebacate bis-2,2,6,6-tetramethylpiperidinol ester 770, added in an amount of 0.1 parts; antacid silane surface coated with magnesium hydroxide 0.15 parts, the coating rate is 5%. The addition amount of barium titanate with a dielectric constant of 3000 is 0.05%, and the particle size is 100nm; EVA resin is added to the mixing tank, and the liquid additive is evenly mixed and sprayed on the EVA particles. After the heating jacket at 45-60℃ is used for insulation and absorption for 2 hours, the anti-acid masterbatch is added and mixed for 2 hours and then allowed to stand. The extruder module temperature is set to 72℃, the film outlet temperature is set to 92℃ for casting, and the screw extrusion speed and metering pump are used to adjust the film weight and thickness.
[0064] Comparative Example 3 provides a high dielectric photovoltaic encapsulation adhesive film and a preparation method thereof, the only difference being that barium titanate and polyvinyl pyrrolidone are directly added to EVA and directly cast.
[0065] Film formula: EVA resin Hanhua 280P (melt index 25, VA content 28) added in an amount of 98 parts; cross-linking agent peroxy-2-ethylhexyl carbonate tert-butyl ester TBEC, added in an amount of 0.4-0.6 parts; auxiliary cross-linking agent TAIC, added in an amount of 0.5 parts; cross-linking promoter propoxylated glycerol triacrylate, added in an amount of 0.6 parts; coupling agent 3-methacryloxypropyl trimethoxysilane, added in an amount of 0.3 parts; light stabilizer sebacate bis-2,2,6,6-tetramethylpiperidinol ester 770, added in an amount of 0.1 parts; antacid silane surface coated with magnesium hydroxide 0.15 parts, the coating rate is 5%. The addition amount of barium titanate with a dielectric constant of 3000 is 0.05%, and the particle size is 100nm; the addition amount of polypyrrolidone polymer is 0.01%, and the molecular weight is 10,000; EVA resin is added to the mixing tank, and the liquid additive is evenly mixed and sprayed on the EVA particles. After the heating jacket at 45-60℃ is kept warm for 2 hours, the anti-acid masterbatch is added and mixed for 2 hours and then allowed to stand. The extruder module temperature is set to 72℃, the film outlet temperature is set to 92℃ for casting, and the screw extrusion speed and metering pump are used to adjust the film weight and thickness.
[0066] Comparative Example 4 provides a high dielectric photovoltaic encapsulation film and a preparation method thereof, the only difference being that barium strontium titanate is directly added to EVA and directly cast.
[0067] Film formula: EVA resin Hanhua 280P (melt index 25, VA content 28) added in an amount of 98 parts; cross-linking agent peroxy-2-ethylhexyl carbonate tert-butyl ester TBEC, added in an amount of 0.4-0.6 parts; auxiliary cross-linking agent TAIC, added in an amount of 0.5 parts; cross-linking promoter propoxylated glycerol triacrylate, added in an amount of 0.6 parts; coupling agent 3-methacryloxypropyl trimethoxysilane, added in an amount of 0.3 parts; light stabilizer sebacate bis-2,2,6,6-tetramethylpiperidinol ester 770, added in an amount of 0.1 parts; antacid silane surface coated with magnesium hydroxide 0.15 parts, the coating rate is 5%. The addition amount of barium strontium titanate with a dielectric constant of 3000 is 0.05%, and the particle size is 50nm; EVA resin is added to the mixing tank, and the liquid additives are evenly mixed and sprayed on the EVA particles. After the heating jacket at 45-60℃ is used for insulation and absorption for 2 hours, the anti-acid masterbatch is added and mixed for 2 hours and then allowed to stand. The extruder module temperature is set to 72℃, the film outlet temperature is set to 92℃ for casting, and the screw extrusion speed and metering pump are used to adjust the film weight and thickness.
[0068] Comparative Example 5 provides a high dielectric photovoltaic encapsulation film and a preparation method thereof, the only difference being that barium strontium titanate and polyvinyl pyrrolidone are directly added to EVA and directly cast.
[0069] Film formula: EVA resin Hanhua 280P (melt index 25, VA content 28) added in an amount of 98 parts; cross-linking agent peroxy-2-ethylhexyl carbonate tert-butyl ester TBEC, added in an amount of 0.4-0.6 parts; auxiliary cross-linking agent TAIC, added in an amount of 0.5 parts; cross-linking promoter propoxylated glycerol triacrylate, added in an amount of 0.6 parts; coupling agent 3-methacryloxypropyl trimethoxysilane, added in an amount of 0.3 parts; light stabilizer sebacate bis-2,2,6,6-tetramethylpiperidinol ester 770, added in an amount of 0.1 parts; antacid silane surface coated with magnesium hydroxide 0.15 parts, the coating rate is 5%. The addition amount of barium strontium titanate with a dielectric constant of 3000 is 0.05%, and the particle size is 100nm; the addition amount of polypyrrolidone polymer is 0.01%, and the molecular weight is 10,000; EVA resin is added to the mixing tank, and the liquid additive is sprayed on the EVA particles after being mixed evenly. After the heating jacket at 45-60℃ is used for insulation and absorption for 2 hours, the anti-acid masterbatch is added and mixed for 2 hours and then allowed to stand. The extruder module temperature is set to 72℃, the film outlet temperature is set to 92℃ for casting, and the screw extrusion speed and metering pump are used to adjust the film weight and thickness.
[0070] The implementation plan and results of adding a single barium strontium titanate high dielectric constant material are shown in the following table:
[0071] .
[0072] Example 5 provides a high dielectric constant photovoltaic encapsulation film and a preparation method thereof, the only difference being that the high dielectric constant material is barium strontium titanate, and the amount used is different.
[0073] Example 6 provides a high dielectric constant photovoltaic encapsulation film and a preparation method thereof, the only difference being that the high dielectric constant material is barium strontium titanate, and the amount used is different.
[0074] The implementation scheme and results of adding two high dielectric constant materials, barium titanate and silicon carbide, are shown in the following table:
[0075] .
[0076] Example 7 provides a high dielectric constant photovoltaic encapsulation film and a preparation method thereof, the only difference being that the high dielectric constant materials are barium titanate and silicon carbide, and the amounts thereof are 0.004% and 0.006% respectively.
[0077] Example 8 provides a high dielectric constant photovoltaic encapsulation film and a preparation method thereof, the only difference being that the high dielectric constant materials are barium titanate and silicon carbide, and the amounts thereof are 0.2% and 0.2% respectively.
[0078] For various high dielectric constant materials: barium titanate, silicon carbide and titanium dioxide, the implementation scheme and results are shown in the following table:
[0079] .
[0080] Example 9 provides a high dielectric constant photovoltaic encapsulation film and a preparation method thereof, the only difference being that the high dielectric constant materials are barium titanate, silicon carbide and titanium dioxide, and the amounts used are 0.002%, 0.005% and 0.003% respectively.
[0081] Example 10 provides a high dielectric photovoltaic encapsulation film and a preparation method thereof, the only difference being that the high dielectric constant materials are barium titanate, silicon carbide and titanium dioxide, and the amounts used are 0.1%, 0.2% and 0.2% respectively.
[0082] Performance Test:
[0083] The encapsulation films prepared in the examples and comparative examples were laminated according to the structure of glass + encapsulation film + TOPCon cell array + encapsulation film + glass to prepare standard photovoltaic modules, and the crosslinking degree of the encapsulation film after lamination was ensured to be >75%.
[0084] Test method for cross-linking degree: according to standard GB / t29848-2018.
[0085] The components made of the encapsulation films of the above embodiments and comparative examples were tested according to IECTS 2804-1:2015. The test conditions were tightened to 85°C, 85% RH, and a negative 1500V constant DC voltage was applied. After 192 hours, the power attenuation of the photovoltaic components before and after the PID test was measured.
[0086] The volume resistivity test method is as follows: a. Use a standard cutter to cut EVA into small samples (200mm*200mm); b. Make laminates according to glass / release film or PTFE cloth / EVA / release film or PTFE cloth / mass production backplane stacking, lamination conditions: 145℃, 15 minutes; c. After lamination, cool and take out the EVA, place it in the test environment for 8 hours, take the uniform part of the middle 150mm*150mm, and test it with a volume resistivity tester. Test conditions: 1000V / min charge, 0.5mA, 120s.
[0087] Adhesion strength test method: a. Make EVA into a laminate (200mm*100mm), and place masking paper between the back panel and EVA, and between EVA and embossed glass; b. After cooling, place the grid mold on the back panel surface, and use a utility knife to cut a small strip (15mm wide) to separate the head of the small strip from EVA, and EVA from the embossed glass; c. Clamp the laminate into the lower fixture and test the peel strength between the back panel and EVA, and EVA and embossed glass (180° peeling, speed 100mm / min); d. Keep the sample intact without midway breakage; e. Take the value when it is stable (test distance: 30~50 mm, effective distance 30±5mm), and record the arithmetic mean data.
[0088] It can be seen from the above description that the above embodiments of the present invention achieve the following technical effects: adding one, two or more high dielectric constant materials such as barium titanate, barium strontium titanate, silicon carbide, lead zirconate titanate, titanium dioxide, zirconium dioxide, silicon dioxide, etc. to the film effectively increases the volume resistivity of the film; on the other hand, the electron displacement polarization effect of the high dielectric constant material is used to resist the electric field strength of the film in the PID test, reduce the change of the electric field inside the film, reduce the ion migration rate, and improve the component PID attenuation.
[0089] Embodiment 11
[0090] A method for preparing a polyvinyl pyrrolidone-high dielectric constant composite film, wherein a high dielectric constant substance is added to a photovoltaic encapsulation polymer material to prepare a polyvinyl pyrrolidone-high dielectric constant composite film, the process comprising:
[0091] Step S1, hydroxylating the surface of a high dielectric constant substance to obtain a high dielectric constant substance a with a hydroxyl group coated on the surface; the high dielectric constant substance is any one of barium titanate, barium strontium titanate, silicon carbide, lead zirconate titanate, titanium dioxide, zirconium dioxide and silicon dioxide, or a mixture of two or more thereof;
[0092] Step S2, performing surface modification treatment on the high dielectric constant material a obtained in step S1:
[0093] Adding a vinyl silane coupling agent to introduce double bonds on the surface of the high dielectric constant material, adding a vinyl pyrrolidone monomer to polymerize the material so that the surface is coated with a polyvinyl pyrrolidone polymer to obtain an active high dielectric constant material b;
[0094] Step S3, mixing the modified high dielectric constant material b and EVA and dissolving them in DMF / dichloromethane solvent, stirring them magnetically at 40±10° C. to obtain a uniform solution, and obtaining a polyvinyl pyrrolidone-high dielectric constant composite film through an electrospinning process.
[0095] The advantage of introducing polypyrrolidone on the surface of the high dielectric constant material covered with hydroxyl groups is that compared with the high dielectric constant material alone, the compatibility of the high dielectric constant material with the EVA film can be enhanced, and polypyrrolidone can enhance the polarization effect of the high dielectric constant material.
[0096] High dielectric constant materials such as barium titanate, barium strontium titanate, and silicon carbide are added to the packaging film, and there are dispersion and compatibility problems. Therefore, the present invention first performs a hydroxylation treatment on high dielectric constant materials such as barium titanate, barium strontium titanate, and silicon carbide, and then performs a modification treatment on them so that their surfaces are coated with polypyrrolidone, thereby enhancing the compatibility of the high dielectric constant materials with the EVA film, and finally prepares a polyvinylpyrrolidone-high dielectric constant composite film through an electrostatic spinning process, and then further prepares a high dielectric photovoltaic packaging film, thereby solving the dispersion and compatibility problems of high dielectric constant materials.
[0097] Compared with the prior art, the advantages of the present invention are: the surface of high dielectric constant materials such as barium titanate, barium strontium titanate, and silicon carbide is modified by coating with organic polymers to improve compatibility with EVA film; the surface of high dielectric constant materials is coated with polypyrrolidone, which does not affect the dielectric properties while activating the polarization effect of the high dielectric constant; the high dielectric layer composite film obtained by electrostatic spinning is hot-pressed with the EVA film to obtain a high dielectric EVA film with better compatibility and dispersibility, which solves the dispersion and compatibility problems of high dielectric constant materials such as barium titanate, barium strontium titanate, and silicon carbide when added to the packaging film. The body resistance of this high dielectric constant EVA packaging film can be significantly increased by 1-2 orders of magnitude; the polarization effect of the high dielectric constant material in the film can significantly improve the anti-PID effect of the component, and the anti-PID effect is close to POE.
Claims
1. A method for preparing a polyvinyl pyrrolidone-high dielectric constant composite film, comprising adding a high dielectric constant material raw material to a photovoltaic encapsulation polymer material to prepare a polyvinyl pyrrolidone-high dielectric constant composite film, characterized in that: The steps include: Step S1, hydroxylating the surface of a high dielectric constant material raw material to obtain a high dielectric constant material a with a surface covered with hydroxyl groups; The surface hydroxylation treatment process of the high dielectric constant material raw material is as follows: the high dielectric constant material raw material and the H2O2 solution are first dispersed by ultrasound, and then stirred at 90-100°C for 3-4 hours by a magnetic stirrer, and the reaction system is cooled to room temperature, the product is filtered and centrifuged with ethanol and deionized water, and then the washed product is placed in a drying oven at 80°C to dry, and the high dielectric constant material a with surface hydroxylation treatment is obtained; The high dielectric constant material raw material is any one of barium titanate, barium strontium titanate, silicon carbide, lead zirconate titanate, titanium dioxide, zirconium dioxide and silicon dioxide, or a mixture of two or more thereof; Step S2, performing surface modification treatment on the high dielectric constant material a obtained in step S1: Adding a vinyl silane coupling agent to introduce double bonds on the surface of the high dielectric constant substance a, adding a vinyl pyrrolidone monomer to polymerize the substance so that the surface is coated with a polyvinyl pyrrolidone polymer to obtain an active high dielectric constant substance b; Step S3, mixing the high dielectric constant material b obtained in step S2 with EVA and dissolving them in a DMF / dichloromethane solvent, stirring them evenly with magnetic force at a temperature of 35-45° C., and then obtaining a polyvinyl pyrrolidone-high dielectric constant composite film through an electrospinning process.
2. The method for preparing a polyvinyl pyrrolidone-high dielectric constant composite film according to claim 1, characterized in that: In the step S2, the high dielectric constant substance a is subjected to a wet surface modification treatment, and the process is as follows: a vinyl silane coupling agent and ethanol are mixed in proportion to obtain a vinyl silane coupling agent solution with a concentration of 0.5-5%, and then an acid catalyst and the high dielectric constant substance a are added and stirred evenly, and the vinyl silane coupling agent is hydrolyzed to react with the surface of the high dielectric constant substance a to introduce double bonds; then vinyl pyrrolidone and a free radical initiator are added, and the mixture is reacted in an ethanol solution at 60-120° C. for 1-3 hours to obtain the high dielectric constant substance b.
3. The method for preparing a polyvinyl pyrrolidone-high dielectric constant composite film according to claim 2, characterized in that: The hydrolysis conditions of the vinyl silane coupling agent are as follows: pH is 3-5, the mass dosage of the vinyl silane coupling agent is 1-10% of the high dielectric constant substance a, and the treatment is carried out at 80° C. for 2 hours; the coverage rate of the high dielectric constant substance a by vinyl pyrrolidone is controlled at 1-10%.
4. The method for preparing a polyvinyl pyrrolidone-high dielectric constant composite film according to claim 1, 2 or 3, characterized in that: The vinyl silane coupling agent is one or both of 171 vinyl trimethoxy silane and 151 vinyl triethoxy silane.
5. The method for preparing a polyvinyl pyrrolidone-high dielectric constant composite film according to claim 1, 2 or 3, characterized in that: In the step S3, during the electrostatic spinning process of the high dielectric constant material b, the spinning voltage is 10-30 kV, the spinning solution flow rate is 1-5 mL / h, and the obtained polyvinyl pyrrolidone-high dielectric constant material composite film is retained on the release paper, and the film thickness is 0.05-0.3 mm.
6. The method for preparing a polyvinyl pyrrolidone-high dielectric constant composite film according to claim 1, 2 or 3, characterized in that: The dielectric constant range of the added high dielectric constant material raw material is: 3-3700; the added amount is 0.001%-0.5% of the mass of the base resin; the particle size is 30-500nm.
7. A high dielectric photovoltaic encapsulation film, characterized in that: The polyvinyl pyrrolidone-high dielectric constant composite film according to claim 1 is laminated between two layers of EVA adhesive films by hot pressing to obtain a three-layer high dielectric constant EVA adhesive film.
8. A method for preparing a high dielectric photovoltaic encapsulation film, characterized in that: The raw materials of the high dielectric photovoltaic encapsulation film include, by weight: 98 parts of EVA resin, 0.4-0.8 parts of cross-linking agent, 0.3-0.8 parts of auxiliary cross-linking agent, 0.4-1.2 parts of accelerator cross-linking agent, 0.2-0.5 parts of coupling agent, 0.05-0.2 parts of light stabilizer, and 0.05-0.4 parts of antacid; The EVA resin has a VA content of 28 and a melt index of 25; The cross-linking agent is one or a mixture of tert-butyl peroxycarbonate-2-ethylhexanoate TAEC and tert-butyl peroxy-2-ethylhexyl carbonate TBEC; The auxiliary cross-linking agent is triallyl isocyanurate TAIC; The crosslinking promoter is one or a mixture of two or more of tripropylene glycol diacrylate, propoxylated glycerol triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate and pentaerythritol tetraacrylate; The coupling agent is one of 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, or a mixture of two or more thereof; The light stabilizer is one of 292 and 770 or a mixture of the two; The antacid is magnesium hydroxide, and the surface of the magnesium hydroxide is coated with silane, with a coating rate of 5%; The EVA resin is added to a mixing tank, and the liquid additive is evenly mixed and then sprayed on the EVA resin. After being heated and absorbed for 2 hours at a heating jacket of 45-60° C., an antacid masterbatch is added, mixed and allowed to stand for 2 hours, and the extruder module temperature is set to 70-75° C. and the film outlet temperature to 90-95° C. for casting. The screw extrusion speed and the metering pump are used to adjust the film weight and thickness to prepare an EVA film; Then the polyvinyl pyrrolidone-high dielectric constant composite film according to claim 1 is laminated between two layers of 200 g EVA films by hot pressing, calendered, and rolled.
9. A photovoltaic module, wherein the photovoltaic module is encapsulated using the high dielectric photovoltaic encapsulation film as claimed in claim 7 or prepared as claimed in claim 8.
Citation Information
Patent Citations
Packaging adhesive film composition, packaging adhesive film and photovoltaic module
CN116640534A
High Dielectric Compositions for Particle Formation and Methods of Forming Particles Using Same
US20140350151A1
Non-woven fiber membranes
US20200173076A1